Analisis Strategi Penyelesaian Pembiayaan Bermasalah Pada Produk Rahn Di KSPPS “BMT Berbagi” Jepara - Rohman, Syifaur; Ansori, Miswan (WADIAH, 2024)
This research aims to identify the factors that cause financing problems and strategies for handling them at the BMT Sharia Savings and Loans and Financing Cooperative (KSPPS) in Jepara. A descriptive qualitative approach is used to describe the problematic financing phenomenon experienced by Islamic financial institutions. Primary data was obtained through interviews and direct observation, while secondary data was collected from financial reports and periodicals. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions according to Miles and Huberman's theory. The research results show that financing problems at KSPPS BMT Sharing are caused by internal factors, such as weak financing analysis, lack of supervision, and suboptimal coordination of the financing committee. External factors include the impact of the COVID-19 pandemic, economic inflation, and the character of members who are irresponsible in paying installments. The handling strategies implemented include preventive measures (financing analysis, monitoring and evaluation), revitalization (rescheduling, restructuring and reconditioning), as well as curative measures (collateral execution, liquidation and collection through third parties). The effectiveness of this strategy is proven by reducing the number of non-performing financing by 19% from 2022 to 2023